Dementia palliative care: A multi-site survey of long term care STAFF'S education needs and readiness to change. (March 2021) - Timmons, S.; O'Loughlin, C.; Buckley, C.; Cornally, N.; Hartigan, I.; Lehane, E.; Finn, C.; Coffey, A.
Abstract: Many people with dementia reside in long-term care, where limited staff knowledge of dementia palliative care has been identified, along with poor awareness that a palliative approach can assist in identifying unmet care needs. Evidence-based guidance in palliative care for people with dementia is available however, implementing this guidance requires staff engagement and a tailored educational approach. This pre-implementation situational analysis informed a tailored staff education intervention to support the implementation of national guidance on dementia palliative care in long term care. Using a cross-sectional study design, underpinned by the Consolidated Framework for Implementation Research, survey data were collected on site profile, staff demographics, learning needs, and readiness-to change at three residential care sites for older people in Ireland. In total, 69 staff (predominantly nurses and healthcare attendants) completed the surveys. Medication management and management of pain were the most frequently identified learning needs. Staff were confident in their ability to implement change but de-motivation and powerlessness were substantial factors as only one-third of staff were "ready for change". Staffing levels, managing risk during change and perceived reluctance in others were common barriers. These results informed an educational intervention to address the specific care context, staff learning needs and barriers to change prior to implementation. Highlights: Staff have significant learning needs in dementia palliative care despite training. The most cited learning needs are for medication and pain management. Staff motivation and powerlessness may influence readiness for change in practice. A programme tailored to learning needs and barriers to change is preferred. This study informed an education intervention in residential care.